Polymerized Ionic Liquid Block Copolymer Electrolytes for All-Solid-State Lithium-Metal Batteries. Issue 7 (21st February 2020) - Mendes, Tiago C.; Goujon, Nicolas; Malic, Nino; Postma, Almar; Chiefari, John; Zhu, Haijin; Howlett, Patrick C.; Forsyth, Maria
Abstract : In this work, we present a polymerized ionic liquid block copolymer (PBCP) film where relevant properties such as ionic conductivity and electrochemical parameters are tailored by using a ternary system comprised of poly(styrene-b-1-((2-acryloyloxy)ethyl)−3-butylimidazolium bis(tri-fluoromethanesulfonyl)imide), LiFSI salt and ethylene carbonate (EC) as a cosolvent. It was found that EC efficiently decreases the glass transition temperature of the ionic block, resulting in an improved ionic conductivity and efficient platting/stripping of lithium. By using an optimal ratio of EC/LiFSI at relatively high LiFSI amount, Li∣Li symmetrical cells at 50 °C show an overpotential as low as 70 mV at 0.1 mA.cm −2 along with a high lithium transport number of 0.56 (tLi + ). All-solid-state full cells based on lithium iron phosphate cathode paired with a lithium metal anode reveal a rather stable cycling at both 50 °C and 70 °C. A negligible capacity fading is observed up to 30 cycles where a specific capacity as high as 161 mAh.g −1 is achieved with a coulombic efficiency of 99.9%. Thus, this work demonstrates an important pathway for tailoring the properties of solid state polymer electrolytes for emerging and specially designed block copolymer architectures comprising domains that give both excellent ionic conduction along with desirable mechanical properties.